Modi$1 (Bs visit to Russia : Its significance and farsighted implicationss - Jain, Vijender (Delhi Prashant Publishing House, 2024)
Prime Minister Narendra Modi$1 (Bs visit to Russia marks a significant chapter in the longstanding relationship between the two nations, underscoring their strategic partnership. The visit carries substantial implications for both regional and global geopolitics, reflecting India$1 (Bs commitment to deepening ties with a key global player while navigating the complexities of international diplomacy. One of the primary outcomes of Modi$1 (Bs visit was the reinforcement of defense and energy cooperation. Russia has long been a crucial supplier of military equipment to India, and this visit further solidified that partnership with new agreements and joint ventures, particularly in advanced technology sectors. Additionally, energy collaboration remains a cornerstone of the relationship, with discussions on expanding India$1 (Bs investment in Russian oil and gas sectors, thereby enhancing India$1 (Bs energy security. On the global stage, Modi$1 (Bs visit is seen as a strategic move to balance India$1 (Bs relationships with major powers like the United States and China. By strengthening ties with Russia, India is positioning itself as a key player in the multipolar world order, advocating for a balanced approach in international relations. The visit also highlighted the importance of cultural and people-to-people exchanges, with initiatives to boost educational and scientific collaboration. In the long run, Modi$1 (Bs visit is likely to have farsighted implications, potentially fostering a more stable and multipolar global order, with India and Russia playing pivotal roles in shaping the future of international politics and economics. (3z(BModi$1 (Bs Visit to Russia: Its Significance and Farsighted Implications(3y (Bdelves into the strategic and diplomatic importance of Prime Minister Narendra Modi$1 (Bs engagement with Russia, exploring the broader geopolitical and economic impacts. CONTENTS 1. Modi$1 (Bs Visit to Russia 2. India-Russia Relations 3. Modi$1 (Bs Visit to Russia : Defense Cooperation and Strategic Alliances 4. Geopolitical Implications and Regional Stability of Modi$1 (Bs Visit in Russia 5. Modi$1 (Bs Visit to Russia: Russia$1 (Bs Role in India$1 (Bs Foreign Policy Strategy 6. Indo-Russian Strategic Partnership for Enhanced Cooperation 7. Exploring New Drivers in India-Russia Cooperation 8. Modi in Russia: Trade, Defence, Energy take Centrestages
Keywords: Prime Minister; Narendra Modi; Foreign Policy